Hubungan Pengetahuan Ibu Dengan Kejadian Stunting Di Puskesmas Mandai Kabupaten Maros (Window of Public Health Journal, 2025)
Stunting is a condition of failure to thrive in toddlers due to chronic malnutrition which is characterized by a z-score value of less than -2 SD. Stunting has short and longterm impacts on children's future health and productivity. The aim of the research is to determine the relationship between maternal knowledge and the incidence of stunting at the Mandai Community Health Center, Maros Regency. This research method uses a quantitative approach with a cross-sectional design. The total sample was 66 respondents, determined using the Slovin formula and stratified random sampling technique. The data collection instrument is a questionnaire through interviews. Data analysis was carried out univariately to see the frequency distribution, and bivariately using the chi-square test to determine the relationship between the maternal knowledge variable (independent variable) and the incidence of stunting (dependent variable) using the SPSS application. The research results show that mother's knowledge is included in the good (50.0%) and poor (50.0%) categories. The chi-square test results show a value of p = 0.511 (p > 0.05), which means there is no significant relationship between maternal knowledge and the incidence of stunting. Conclusion There is no significant relationship between the level of maternal knowledge and the incidence of stunting. It is hoped that ongoing education for parents can increase understanding about nutrition and stunting prevention.